Learn tennis in a weekend - Douglas, Paul (London : Dorling Kindersley, 1991)
Part of a series that offers a concentrated course for the beginner, which is intended to be completed in 48 hours. This book outlines the basic terms and techniques of tennis and outlines more advanced techniques. Other books in the series include "Sailing" and "Golf".
-- Tennis kit -- On the court -- Tennis training -- Get to grips -- Stance and control -- Basic ball sense -- Forehand drive -- Backhand drive -- Double-handed backhand -- The service -- Service return -- Forehand volley -- Backhand volley -- Lob defence -- Smash attack -- Approach play -- Serve and volley -- Playing the game -- Playing doubles -- Advanced strokes.
"A Dorling Kindersley book"--Verso t.p.
Includes index.
Keywords: Tennis